Comparison of luminescence properties of ZnO nanorods, obtained by hydrothermal method and pulse electrochemical method - Afanasyev, D.A.; Aitymov, Zh.K.; Ilyassov, B.R.; Ibrayev, N.Kh. (KSU Publ., 2017)
Influence of of the method of synthesis of ZnO rods on their microstructure and spectral-luminescent properties was studied in the work. Pulsed electrochemical and hydrothermal methods were used. The films with a similar value of thickness both methods have been obtained. The diameter of the rods obtained by the hydrothermal method is much smaller than the diameter of rods obtained by the electrochemical method. It is seen from microscopic measurements. X-ray diffraction was measured for ZnO films obtained by pulsed electrochemical method. Crystalline ZnO films with a wurtzite structure are obtained both by hydrothermal and pulsed electrochemical methods. The absorption and fluorescence spectra were measured for the samples. Bandgaps of films are determined from the absorption spectra. Edge luminescence in the ultraviolet region of the spectrum, having an exciton nature and defect luminescence in the visible spectral region is observed in the luminescence spectra of films. Analysis of the absorption and luminescence spectra showed that defectiveness ZnO film make by the electrochemical method is significantly higher film defects make by hydrothermal method.
Гидротермалдық жəне импульсті электрохимиялық əдіспен алынған ZnO наноөзекшенің люминесценттік қасиеттерін салыстыру
Сравнение люминесцентных свойств наностержней ZnO, полученных гидротермальным и импульсным электрохимическим методами
Keywords: thin film of ZnO; absorption spectrum; luminescence; hydrothermal synthesis; pulse electrochemical synthesis; defectiveness.